2013
DOI: 10.11648/j.aff.20130205.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eucalyptus tereticornis, Tagetes minuta and Carica papaya as Stored Maize Grain Protectants against Sitophilus zeamais (Motsch.) (Coleoptera: Curculionidae)

Abstract: Sitophilus zeamais (Motsch.) is an important storage pest of maize grain in several parts of Africa including Zimbabwe. Although synthetic pesticides are effective at controlling the pest, environmental and health hazards of these chemicals are of increasing concern. The study assessed efficacy of botanical leaf powders of Eucalyptus tereticornis, Tagetes minuta and Carica papaya in controlling S. zeamais using rates of 5 g, 10 g and 20 g per 200 g of open pollinated maize grain (variety ZM421). The trial was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…Several studies have indicated efficacy of leaf powders and essential oils of most Eucalyptus spp. against many insect species including storage pests (Muzemu et al, 2013;Rajendran and Sriranjini, 2008;Mulungu et al, 2007;Talukder, 2006;Modgil and Samuels, 1998). Eucalyptus spp leaf powders for example, were shown to protect wheat grain against insect pests (Sitophilus oryzae (L.) Coleoptera: Curculionidae), Sitotroga cereallella (Olivier) Lepidoptera: Gelechiidae) and Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) for five months while essential oils of Eucalyptus camaldulensis and E. leucoxylon were shown to be lethal to the dates pest carob moth Ectomylois ceratoniae (Zeller) (Lepidoptera: Pyralidae) (Ben-Jemâa et al, 2013;Modgil and Samuels, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated efficacy of leaf powders and essential oils of most Eucalyptus spp. against many insect species including storage pests (Muzemu et al, 2013;Rajendran and Sriranjini, 2008;Mulungu et al, 2007;Talukder, 2006;Modgil and Samuels, 1998). Eucalyptus spp leaf powders for example, were shown to protect wheat grain against insect pests (Sitophilus oryzae (L.) Coleoptera: Curculionidae), Sitotroga cereallella (Olivier) Lepidoptera: Gelechiidae) and Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) for five months while essential oils of Eucalyptus camaldulensis and E. leucoxylon were shown to be lethal to the dates pest carob moth Ectomylois ceratoniae (Zeller) (Lepidoptera: Pyralidae) (Ben-Jemâa et al, 2013;Modgil and Samuels, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These include Lippia javanica L. (Gadzirayi et al, 2006), Lantana camara L. (Fusire, 2008) and T. minuta (Muzemu et al, 2013) leaves. Several studies have investigated the efficacy of Eucalyptus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that 59.37% out of 30,000 plants documented in the Royal Botanical Garden, Kew, UK, were found to have medicinal use. Many researchers have performed various studies of insecticidal plants for evaluating the properties and their effectiveness as repellents and antifeedants, and for their toxicity against various storage insects …”
Section: Introductionmentioning
confidence: 99%
“…In global, maize is an important crop for a small-scale farmer as food and feed resource (Mwololo et al, 2012). According to Muzemu, Chitamba, & Mutetwa (2013), maize is also the most important crop in Africa that significantly contributes to the national production. Markham, Bosque-Perez, Borgemeister, & Meikle (1994) mentioned that in Africa, losses by storage insect pests i.e.…”
Section: Introductionmentioning
confidence: 99%